IMPLEMENTATION OF AI TECHNOLOGY IN DIGITAL TRANSFORMATION OF MARKETING STRATEGY: A LITERATURE REVIEW - Nina Triolita; Al-Amin (CV. Adiba Aisha Amira, 2025)
The implementation of artificial intelligence (AI) technologies in the digital transformation of marketing strategies is increasingly the focus of attention of researchers and business practitioners. This research reviews the current literature on the application of AI in marketing, highlighting how this technology can improve operational efficiency and effectiveness of marketing decisions. Through the literature review, AI provides companies with the ability to devise marketing strategies that are more targeted and responsive to market changes. However, the adoption of AI poses challenges such as the need for technical expertise and concerns over data privacy issues. This study underscores that the successful integration of AI in marketing requires a balance between technological innovation and effective risk management.